Sandur Manduro From Ritual To Tourism Art - Trinil Windrowati; Suwandi Widianto (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2022)
The traditional theater performing art, Sandur Manduro which originated from the people’s spontaneity of Manduro Village, Kabuh District, Jombang Regency, is formed by their life cycle. Numerous artistic components, including Fine Arts, Literary Arts, Musical Arts, and Dance arts, may be found in Sandur Manduro. However, the ritualistic purpose of Sandur Manduro's art is currently experiencing a decline in performances. Three (3) issues need to be addressed, including 1) Its performing duration lasts for about roughly eight hours, 2). Sandur Manduro, whose initial acts as a ritual function of Ngudari Kata may turn into a performance/entertainment function, 3) there is no regeneration for the older players of Sandur Manduro. Through the Community Partnership Program (PKM), it is expected to be an independent performance by revitalizing it into an art of tourism and training it to the younger generations of Manduro Village. To revitalize this, the authors adopted Adolph S. Tomars's conceptual framework of Tourism Art that is: 1) Compaction, 2) copy of the original, 3) elimination of sacred and symbolic values for glamorous, 4) diversity, and 5) affordability.